Effect of hard-plate rolling and annealing treatment on the microstructure and mechanical properties of NbB2 particle-reinforced AZ91 composite - Fan, Wenxue; Bai, Yu; Li, Tianxin; Hao, Hai; Zhang, Xingguo (Journal of magnesium and alloys, 2025)
•The NbB2/AZ91 composite exhibiting desirable mechanical properties was fabricated using hard plate rolling and a subsequent short-term annealing process.•The NbB2 particles exhibited a remarkable grain refinement effect on both as-cast, as-rolled and as-annealed AZ91 alloy. The tensile properties of the as-rolled and as-annealed AZ91 alloy were also significantly improved with the NbB2 particles.•The NbB2 particles could promote dynamic recrystallization, and precipitation of fine Mg17Al12 phases by particle-stimulated nucleation effect during hard plate rolling process.•The strengthening mechanisms of NbB2/AZ91 composites were mainly due to the grain refinement strengthening, hetero-deformation induced strengthening, and strengthening induced by particles and mismatch coefficient of thermal expansion strengthening.•The texture weakening, more activation of non-basal slip systems, and more uniform strain patterns were the main reasons for the enhancement of ductility. In this study, a NbB2/AZ91 composite exhibiting desirable mechanical properties was fabricated using a sample casting technique, followed by hard-plate rolling and short-term annealing. The effect of NbB2 particles on the microstructural evolution of the AZ91 alloy was investigated. The presence of NbB2 was shown to have a grain-refining effect on the AZ91 alloy and promoted dynamic recrystallization (DRX) and precipitation of fine Mg17Al12 phases via particle-stimulated nucleation (PSN). Tensile testing revealed substantial enhancements in the ultimate tensile strength (UTS), yield strength (YS), and elongation (EL) of the as-rolled AZ91 alloy, with values of 379 MPa, 292 MPa, and 14.7%, respectively, owing to the incorporation of NbB2 particles. Annealing led to further enhancements in EL with slight reductions in UTS and YS (360 MPa, 252 MPa, and 16.8%, respectively). Owing to grain refinement and the PSN effect of the NbB2 particles, a significant number of geometrically necessary dislocations (GNDs) were induced in the matrix during the rolling process, which reduces the nucleation barrier and increases the number of nucleation sites for the recrystallized grains and Mg17Al12 precipitates. Meanwhile, many residual dislocations and fine Mg17Al12 precipitates in the as-rolled alloys were annihilated during annealing, resulting in slight grain growth and coarsening. The strengthening mechanism of the NbB2/AZ91 composite are mainly associated with grain-refinement strengthening, particle-induced dislocation strengthening, strengthening resulting from mismatching coefficients of thermal expansion (CTE), and hetero-deformation-induced (HDI) strengthening. Textural weakening, increased activation of non-basal slip systems, more-uniform strain patterns resulting from NbB2 particles, and precipitation are mainly responsible for enhancing ductility. [Display omitted]